Others Knowing Others / Perspectives on Ethnographic Careers - Fowler Don D; Hardesty Donald L (Smithsonian Institution Press, 1994)
Ten senior anthropologists present a composite portrait of cultural anthropology since World War II, recounting how changes in the discipline have opened up new approaches and new problems. Preface, Introduction, Honored Guest and Marginal Man: Long-Term Field Research and Predicaments of a Native Anthropologist, Interpreting Skulls: Reflections of Fieldwork in Malaysia, Changes owner Time in an African Culture and in an Anthropologist, Time on Our Hands, Beginning to Understand: Twenty-Eight Years of Fieldwork in the Great Basin of Western North America, Years and Careers, Reflections on Fieldwork with Little People of America: Myths and Methods, Afterthoughts, Contributors.